2017
DOI: 10.1111/are.13582
|View full text |Cite
|
Sign up to set email alerts
|

Dietary available phosphorus requirement for juvenile gibel carp (Carassius auratus gibeliovar. CASIII)

Abstract: A 57-day growth experiment was conducted with juvenile gibel carp (13.48 AE 0.10 g) in a flow-through system to study the effect of dietary phosphorus on growth performance, body composition, nutrition utilization, phosphorus loading and enzymes activities. Seven semipurifed diets were formulated to contain 0.07 (the basal), 2. 27, 5.32, 8.10, 12.06, 15.24 and 19.48 g available phosphorus/kg diet.The results showed that specific growth rate, body length and feed efficiency significantly increased in the fish f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
(61 reference statements)
5
4
0
Order By: Relevance
“…The improvement in PUE up to 6.5 g/kg and then decrease in PUE as observed in this study is in line with the results reported in previous studies (Nordrum et al 1997;Satoh et al 2003;Luo et al 2009Luo et al , 2010Xie et al 2017). However, fish fed lower and higher levels of dietary phosphorus than 6.5 g/kg showed lower PUE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The improvement in PUE up to 6.5 g/kg and then decrease in PUE as observed in this study is in line with the results reported in previous studies (Nordrum et al 1997;Satoh et al 2003;Luo et al 2009Luo et al , 2010Xie et al 2017). However, fish fed lower and higher levels of dietary phosphorus than 6.5 g/kg showed lower PUE.…”
Section: Discussionsupporting
confidence: 92%
“…However, fish fed lower and higher levels of dietary phosphorus than 6.5 g/kg showed lower PUE. Similar to our study, Xie et al (2017) also reported a quadratic responses between the phosphorus retention efficiency and the dietary phosphorus levels in gibel carp. The improvement in PUE up to 6.5 g/kg and then decrease in PUE as observed in this study is in line with the results reported in previous studies (Nordrum et al 1997;Satoh et al 2003;Luo et al 2009Luo et al , 2010Xie et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The results indicated that the excessive amount of P intubation led to an increase in P excretion and prolonged P elimination time of hybrid sturgeon. The discharging of P due to the excessive P supplementation has been a big concern that contributed to the eutrophication of aquatic environments and consequently the deterioration of water quality (Rodehutscord et al, ; Xie et al, ). P waste excretion in fish is usually evaluated indirectly in nutrition study by assessing the digestibility of feed, which, however, could be affected by the faecal collection time and methods (Hua & Bureau, ), while the urine collection method in this study provides a possibility of evaluating P waste discharging directly and accurately in fish and a better understanding of P utilization in nutrition study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to minimize eutrophication of waterbody, aquafeeds should meet the P requirement of fish and avoid excess P contents in the diet at the meantime (Jokinen, Vielma, Aaltonen, & Koskela, ; Musharraf & Khan, ). The studies about P requirement and utilization have been largely reported in many fish species, such as large yellow croaker ( Pseudosciaena crocea R. ) (Mai et al, ), rainbow trout ( Oncorhynchus mykiss ) (Fontagné et al, ; Lellis, Barrows, & Hardy, ), juvenile black seabream ( Sparus macrocephalus ) (Shao et al, ), Africa catfish ( Heterobranchus bidorsalis ) (Nwanna, Adebayo, & Omitoyin, ), stinging catfish ( Heteropneustes fossilis ) (Zafar & Khan, ) and gibel carp ( Carassius auratus gibelio ) (Xie et al, , ), which, however, have rarely been studied in sturgeon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation